The Family Nagashi: Anti-racist radio and the Japanese internment. (1st October 2018) - Killmeier, Matthew A.
This article provides a cultural history of The Family Nagashi, a 1945 propaganda play by Arch Oboler focused on combatting racism against Japanese Americans returning home from the wartime internment camps and military service. It situates the play in the historical contexts of wartime US racism towards Japanese Americans, the collaborative nature of US wartime propaganda and the uses of ethnic soldiers in wartime propaganda to promote tolerance. The author argues that the play provides a poetic argument that relies heavily on an affective narrative to support the efforts of the US government to resettle Japanese Americans immediately after the war. The play draws on materials provided by the US government, which was a common collaborative practice in wartime propaganda, in its attempt to persuade listeners that Japanese Americans are assimilated Americans, to combat racism against them and to forward a message of tolerance and pluralism.